Visualization of c-di-GMP in multicellular Dictyostelium stages - Ide, Hayato; Hayashida, Yukihisa; Morimoto, Yusuke V. (Frontiers in Cell and Developmental Biology, 2023)
The bacterial signaling molecule cyclic diguanosine monophosphate (c-di-GMP) is only synthesized and utilized by the cellular slime mold Dictyostelium discoideum among eukaryotes. Dictyostelium cells undergo a transition from a unicellular to a multicellular state, ultimately forming a stalk and spores. While Dictyostelium is known to employ c-di-GMP to induce differentiation into stalk cells, there have been no reports of direct observation of c-di-GMP using fluorescent probes. In this study, we used a fluorescent probe used in bacteria to visualize its localization within Dictyostelium multicellular bodies. Cytosolic c-di-GMP concentrations were significantly higher at the tip of the multicellular body during stalk formation.